DIGITALISASI DAKWAH: STRATEGI KOMUNIKASI PONDOK PESANTREN LIRBOYO DALAM MENANAMKAN NILAI MODERASI DI MEDIA SOSIAL - Yudi Hartono (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study examines the digital da'wah communication strategy of Lirboyo Islamic Boarding School in instilling the values of religious moderation through social media. By utilizing various digital platforms such as Instagram, YouTube, TikTok, and Facebook, this Islamic boarding school has successfully bridged traditional Islamic values with the communication needs of today's generation. The focus of the study covers three main aspects: (1) the form and pattern of digital da'wah, (2) moderate da'wah communication strategies, and (3) the values of religious moderation instilled through digital content. The results of the study show that Lirboyo Islamic Boarding School consistently applies the principles of tawassuth, tasamuh, tawazun, and i'tidal in every digital da'wah content produced, while remaining based on yellow books and the opinions of authorized scholars..